PERAN MODERASI KUALITAS AUDIT PADA PENGARUH KONEKSI POLITIK TERHADAP NILAI PERUSAHAAN - Stanesie Liyanto; Fransiskus Eduardus Daromes; Alfonsus Jantong (Universitas Agung Podomoro, 2022)
The purpose of this study is to analyze and test whether political connection has an influence on firm value and to analyze and test whether audit quality can moderate the relationship between political connection to firm value. The population used in this study is manufacturing companies listed on the Indonesia Stock Exchange (IDX) with a research period 2016-2019. This study using purposive sampling method and secondary data. The number of samples is 108 companies every year. Regression analysis used to analyze data is performed using the moderated regression analysis (MRA). The results of this study indicate that political connection has a positive and significant influence on firm value. Audit quality cannot moderate the effect of political connection on firm value.